Species diversity of macroalgae in Grønfjorden, Spitsbergen, Svalbard - Svetlana V. Malavenda (Polar Research, 2021)
Climate changes in the North Atlantic and Arctic affect the macrophytobenthos along with other components of the ecosystem, resulting in an increase of species diversity and biomass in western Spitsbergen, as has been reported. Grønfjorden is located at the mouth of one of the largest fjords of Spitsbergen, Isfjorden, and is influenced by the recent significant increase in the inflow of Atlantic Water. However, there are nearly no published data on the phytobenthic communities in this area. This research study of the littoral and sublittoral areas of Grønfjorden in 2013–14 documented 68 species, mostly high-boreal and boreal–Arctic species. When compared with species diversity in the other areas of western Spitsbergen, the data show the uniqueness of Grønfjorden’s species composition.